Small Cell Transformation and T790M Mutation as Coresistance Mechanisms for First-line Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitor (TKI) Therapy Failure - Chee, Shee Chai (Elsevier Inc., 2017)
Discovery of the activating EGFR mutation gene has revolutionized the treatment of patients with NSCLC. Nevertheless, resistance to first-line EGFR tyrosine kinase inhibitors (TKIs) develops in most patients with EGFR-mutant NSCLC after a period of 9 to 13 months. Here, we reported a case of first-line EGFR TKI failure attributed to SCLC transformation and T790M mutation